Odpowiedzi

2011-07-14T18:25:50+02:00

1a

-(x+1)+(2x+4)=-x-1+2x+4=x+3

b]

3(a²-4)-(a²+2)=3a²-12-a²-2=2a²-14=

c]

2(a+3b)-4a(2-7b)=2a+6b-8a+28ab=-6a+6b+28ab

d]

(2a+4)(3b+7a-3)=6ab+14a²-6a+12b+48a-12=14a²+42a+12b+6ab-12

zad.2:

3x²-6x+7

x=2

3×2²-6×2+7=27-12+7=22

  • Użytkownik Zadane
2011-07-14T19:05:03+02:00

1.

a)-(x+1)+(2x+4)=-x-1+2x+4=x+3

b)2(a2-4)-(-a2+2)=2a2-8+a2-2=3a2-10

c)2(a+3b)-4a(2-7b)=2a+6b-8a+28b=-6a+34b

d)(2a+4)*(3b+7a-3)=2ab+14a2-6a+12b+28a-12=14ab+14a2+22a-12

 

3x2-6x+7=3*2*2-6*2+7=12-12+7=7